(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
In this article, the concept of speech culture and its importance in higher education is discussed. Higher education today speech should be clear and concise, strictly ordered, understandable for everyone. Own the wordsUsing it instead increases the effectiveness of the word, quickly conveying the essence of the story serves to get